THE IMPACT OF FINANCIAL INSTITUTIONS ON ECONOMIC GROWTH AND FINANCIAL STABILITY (Yearbook - Faculty of Economics, 2018)
The success of the efficient functioning of financial institutions within the financial system, affect the living standards and welfare of each individual in the society. Financial institutions are those that collect the savings of the people and allocate to the economic agents that have profitable investment opportunities, increasing the production capacity of the economy. Financial institutions also allow economic agents to postpone their current consumption in the future (stimulating their savings), and on the other side at the same time, allow consumers to spend more than their level of disposable income (through loans to customers). The efficient functioning of the financial system and financial institutions and their effects of economies of scale and lower operating (information and transaction) costs of the financial market, provide rapid economic growth. Likewise, improper functioning of financial institutions and financial system pulls insufficient mobilization of funds, decline in consumption, decline in production, insufficient utilization of available resources, decline in employment and a reduced standard of living.